32-week premature rupture of membranes caused by oropharyngeal microbiota. (12th October 2017) - Hidalgo-Chicharro, Alberto; Abad-Torreblanca, Raquel; Navarro-Marí, José María; Gutiérrez-Fernández, José
Abstract : Introduction. Preterm premature rupture of membranes (PPROM) usually has a multifactorial etiology that is often unknown, although the most frequently reported cause is infection by group B Streptococcus . Therefore, the etiology of PPROM, although probably infectious, remains unknown in most cases. This case describes a PPROM caused by infection from oropharyngeal microbiota. Case presentation. We report the case of a 26-yr-old pregnant woman. The gestational age was 32 weeks+5 days. Examinations in the emergency department revealed the release of clear amniotic fluid and a closed multiparous cervix with a length of 22 mm. Endocervical culture evidenced the growth of Staphylococcus aureus, serogroup B Neisseria meningitidis and Haemophilus influenzae . Conclusion. Preventive antibiotic therapy should consider: opportunistic infections by normal genital microbiota, infections due to sexual activity, opportunist microorganisms derived from oral sex, and the hematogenous spread of oral bacteria.